The left song book - Bush, Alan; Workers' Music Association; Swingler, Randall (London : Victor Gollancz, 1938)
Bibliotheek Camille Huysmans
Bevat: partituren
Engels
Brochure
Keywords: liederenbundel; partituren; strijdliederen; arbeidersliederen